SISTEM PAKAR DIAGNOSA INFEKSI SALURAN PERNAFASAN PADA BALITA MENGGUNAKAN BAYESIAN NETWORK - honggowibowo, anton setiawan (Sekolah Tinggi Teknologi Adisutjipto, 2017)
At present in developing countries, especially in Puskesmas very rarely encountered health workers, especially specialists. Though parents are in need of specialists, especially a specialist in the field of child health sciences. Puskesmas officials often have difficulty in deciding what diseases suffered by children because of lack of knowledge about the types of infectious diseases caused by bacteria. This is where the role of an expert or an expert in the field of childhood disease is needed. Therefore, to handle the problem it requires an expert system to diagnose respiratory infections in infants so that this system can be used to diagnose respiratory infections in infants using Bayesian Network method to determine what kind of illness and how to solve it. Maksimal 200 kata berbahasa Inggris dicetak miring dengan Times New Roman 10 point. Abstrak harus jelas, deskriptif, dan harus memberikan gambaran singkat masalah yang diteliti. Pada umumnya harus diikuti dengan pernyataan tentang metodologi dan ringkasan singkat hasil penelitian. Abstrak harus diakhiri dengan komentar tentang pentingnya hasil atau kesimpulan singkat.